1992
DOI: 10.1104/pp.100.3.1296
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphoinositide Phospholipase C in Plasma Membranes of Wheat (Triticum aestivum L.)

Abstract: Polyphosphoinositide-specific phospholipase C activity was present in plasma membranes isolated from different tissues of several higher plants. Phospholipase C activities against added phosphatidylinositol 4-phosphate (PIP) and phosphatidylinositol 4,5-bisphosphate (PIP2) were further characterized in plasma membrane fractions isolated from shoots and roots of dark-grown wheat (Triticum aestivum L. cv Drabant) seedlings. In right-side-out (70-80% apoplastic side out) plasma membrane vesicles, the activities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…2) and thus give access to the phosphoinositide substrate. Mg 2ϩ ions are known to activate PI-PLC activity in the presence of 10 m Ca 2ϩ in wheat plasma membranes (Pical et al, 1992;Jones and Kochian, 1995). In contrast, Al 3ϩ is a strong inhibitor of PI-PLC activity in preparations of plasma membranes from wheat roots (Jones and Kochian, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2) and thus give access to the phosphoinositide substrate. Mg 2ϩ ions are known to activate PI-PLC activity in the presence of 10 m Ca 2ϩ in wheat plasma membranes (Pical et al, 1992;Jones and Kochian, 1995). In contrast, Al 3ϩ is a strong inhibitor of PI-PLC activity in preparations of plasma membranes from wheat roots (Jones and Kochian, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The PI-PLC assay was performed according to the method of Melin et al (1992) and Drøbak et al (1994). The reaction mixture contained 50 mm Tris/maleate, pH 6.25, 0.2 mm of 3 H-head-group-labeled PI or PIP 2 at approxi-mately 5000 dpm nmol Ϫ1 (Amersham) and varying amounts of Ca 2ϩ in a volume of 50 L. A 0.6 mm micellar lipid stock solution was prepared by mixing unlabeled (PI, PIP 2 ; Sigma) and 3 H-labeled lipid in chloroform:methanol (2:1, v/v), evaporation of solvent under a stream of nitrogen, addition of 166 mm Tris/maleate, pH 6.25, and sonication for 10 min.…”
Section: Biochemical Analysis Of Recombinant Stplcsmentioning
confidence: 99%
See 1 more Smart Citation
“…PI-PLC activity was measured as described (36). The reaction mixture contained 50 mM Tris-maleate (pH 6.0-6.5), 0.2 mM phosphatidyl[2-3 H]inositol-4,5-bisphosphate (1,000-2,000 dpm͞nmol) in micellar solution, 10 M free Ca 2ϩ , 80 mM KCl, 1.5 mM MgCl 2 , and 0.1-0.5 g of recombinant protein.…”
Section: Methodsmentioning
confidence: 99%
“…PLC is a family of isoenzymes that has been classified into three groups: ␤, ␥, and ␦ (Rhee and Bae, 1997). In plants several studies have reported the biochemical presence of this enzyme (McMurray and Irvine, 1988;Tate et al, 1989;Melin et al, 1992;Pical et al, 1992;Yotsushima et al, 1992Yotsushima et al, , 1993Huang et al, 1995;De Los Santos-Briones et al, 1997). Different genes for PLC have also been cloned (Hirayama et al, 1995(Hirayama et al, , 1997Shi et al, 1995;Yamamoto et al, 1995;Kopka et al, 1998), all of them resembling the ␦ type.…”
Section: Camentioning
confidence: 99%